RANCANG BANGUN SISTEM INFORMASI PENJUALAN MEUBEL (STUDI KASUS: CV. FAJAR INDAH AMUNTAI) - Windarsyah; Muhammad Alkaff (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2016)
One of the media information that is widely used by some companies today is desktop-based information systems where an application is expected to help facilitate in resolving a problem. Furniture Fajar Indah Amuntai in managing goods data, pricing and reporting the results of the transaction is still using paper media or notebook in storing such data, however, when there are changes in prices of goods then the data is written back in a new book, so the time and cost of wasted writing and buying new books. To identify the needs of the system in this study using data flow trending analysis. From the information obtained by the analysis conducted inputs, outputs and system processes that are expected, which is a facility operator to manipulate data, manipulate data items, records every sales transaction, it can display and print the report. With the analysis results can be obtained interface design is more user friendly and easy to use.